2021
DOI: 10.1007/s10499-021-00751-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Streptococcus sp. and antibiotic resistance genes present in Tilapia farms (Oreochromis niloticus) from the Northern Pacific region, Costa Rica

Abstract: Streptococcosis is a bacterial disease in tilapia that produces economic losses, caused mainly by Streptococcus agalactiae and S. iniae. It is treated using oxytetracycline and florfenicol, which when inappropriately used promotes the selection of antibiotic resistance genes (ARGs). The disease has been mainly associated with stress events such as variations in temperature. The aims of the present study were (1) to detect by molecular methods two species of Streptococcus sp. in a tilapia farm, (2) to relate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
0
6
0
1
Order By: Relevance
“…Notably, the plasmid metagenomic focusing on the mobile genetic elements (MGEs) may have great potential to identify ARGs in complex environments ( Liu et al, 2019 ). Meanwhile, Oviedo-Bolaños collected 450 individuals from tilapia ponds and organ pools in the Northern Pacific region, Costa Rica, and identified ARGs (including tet M, tet O, fex A, and erm B) by the PCR method ( Oviedo-Bolaños et al, 2021 ). The results showed that S. iniae was not detected, and 60% of the ponds and 46% of the organ pools were positive for Streptococcus agalactiae with tet O (29.1%), and tet M (12.7%) and erm B (1.8%), respectively.…”
Section: Bacterial Resistance To Antibiotics In Food Animal Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the plasmid metagenomic focusing on the mobile genetic elements (MGEs) may have great potential to identify ARGs in complex environments ( Liu et al, 2019 ). Meanwhile, Oviedo-Bolaños collected 450 individuals from tilapia ponds and organ pools in the Northern Pacific region, Costa Rica, and identified ARGs (including tet M, tet O, fex A, and erm B) by the PCR method ( Oviedo-Bolaños et al, 2021 ). The results showed that S. iniae was not detected, and 60% of the ponds and 46% of the organ pools were positive for Streptococcus agalactiae with tet O (29.1%), and tet M (12.7%) and erm B (1.8%), respectively.…”
Section: Bacterial Resistance To Antibiotics In Food Animal Farmsmentioning
confidence: 99%
“…It is favorable to improve the knowledge of the diseases infected with Streptococcus sp. and to efficiently prevent and control these pathogens in tilapia farming worldwide ( Oviedo-Bolaños et al, 2021 ).…”
Section: Bacterial Resistance To Antibiotics In Food Animal Farmsmentioning
confidence: 99%
“…Oxytetracycline is a natural broad-spectrum antibiotic extensively used in global aquaculture due to its limited side effects in the host and broad-spectrum activity against both Gram-negative and Gram-positive bacteria, through the inhibition of protein syn-thesis [11][12][13]. In tilapia, OTC has been shown to successfully treat a range of bacterial diseases including Francisellosis, motile Aeromonas septicemia, and Streptococcosis, which are significant disease challenges for this sector [14][15][16]. Across the global aquaculture industry, OTC is often administered orally in the diet during disease outbreaks, where doses range 50 to 250 mg/kg/day for typically between four and eight days, up to 21 days, depending on the fish species and farming country [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended antibiotics for the treatment of V. parahaemolyticus are tetracycline or ciprofloxacin, which can also be used in severe or prolonged disease of V. parahaemolyticus (see review by Elmahdi et al, 2016). However, the increasing diversity of ARGs in aquatic gut microorganisms has been reported in recent studies based on polymerase chain reaction (PCR) and metagenomic analysis (e.g., Liu et al, 2019; Oviedo‐Bolaños et al, 2021). In addition to Aeromonas , the ARGs in the intestinal bacteria of shrimp are also mainly derived from Vibrio (accounting for 2.8%–51%) plasmids (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%